Exploring Victorian travel literature : disease, race and climate - Howell, Jessica (Edinburgh : Edinburgh University Press, 2014)
This interdisciplinary study explores both the personal and political significance of climate in the Victorian imagination. It analyses foreboding imagery of miasma, sludge and rot across non-fictional and fictional travel narratives, speeches, private journals and medical advice tracts. Well-known authors such as Joseph Conrad are placed in dialogue with minority writers such as Mary Seacole and Africanus Horton in order to understand their different approaches to representing white illness abroad. The project also considers postcolonial texts such as Wilson Harris's Palace of the Peacock to demonstrate that authors continue to 'write back' to the legacies of colonialism by using images of climate induced illness. Key Features. Offers a new perspective on the study of Victorian literature and imperialism by studying depictions of white bodies made ill by the tropical environment Bridges the critical approaches of illness narrative analysis, race and travel studies Analyses canonical travel literature alongside works by lesser known and minority authors Shows the pervasive afterlife of climate in the cultural imagination, even after the discoveries of germ theory and contagionism
Includes bibliographical references (pages 173-183) and index.
Print version record.
English.
JSTOR
Keywords: Travelers' writings, English -- History and criticism; English literature -- 19th century -- History and criticism; Travel in literature; Medicine and the humanities -- Africa -- 19th century; Medicine in literature; Africa; Medicine in Literature; Travel -- history; Environment; History, 19th Century; Tropical Climate; Africa; Écrits de voyageurs anglais -- Histoire et critique; Littérature anglaise -- 19e siècle -- Histoire et critique; Voyage dans la littérature.; Médecine et sciences humaines -- Afrique -- 19e siècle.; Médecine dans la littérature.; Médecine -- Histoire -- 19e siècle.; Afrique; LITERARY CRITICISM -- General; Medicine in literature; English literature; Medicine and the humanities; Travel in literature; Travelers' writings, English; Africa; English; Languages & Literatures; English Literature; 1800-1899; Criticism, interpretation, etc